2017
DOI: 10.1088/1361-6544/aa675b
|View full text |Cite
|
Sign up to set email alerts
|

Parameter shifts for nonautonomous systems in low dimension: bifurcation- and rate-induced tipping

Abstract: We discuss the nonlinear phenomena of irreversible tipping for non-autonomous systems where time-varying inputs correspond to a smooth "parameter shift" from one asymptotic value to another. We express tipping in terms of properties of local pullback attractors and present some results on how nontrivial dynamics for non-autonomous systems can be deduced from analysis of the bifurcation diagram for an associated autonomous system where parameters are fixed. In particular, we show that there is a unique local pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
183
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(186 citation statements)
references
References 39 publications
2
183
1
Order By: Relevance
“…In our numerical study this probability is P = 0.85, indicating that the Snowball Earth is the more probable outcome. This is in contrast to the way tipping transitions are usually discussed in deterministic systems, where as a result of a monotonous parameter drift, either all trajectories tip, or none of them do 40 .…”
Section: The Ensemble View: Visualizing the Snapshot Attractormentioning
confidence: 75%
“…In our numerical study this probability is P = 0.85, indicating that the Snowball Earth is the more probable outcome. This is in contrast to the way tipping transitions are usually discussed in deterministic systems, where as a result of a monotonous parameter drift, either all trajectories tip, or none of them do 40 .…”
Section: The Ensemble View: Visualizing the Snapshot Attractormentioning
confidence: 75%
“…The scenario (12) corresponds to an infinite rate of change in the parameter (the forcing amplitude u) at time t = 750 kyr BP. For this scenario Ashwin et al [3] developed the concept of breakdown of basin forward stability, which generalizes the scenario described above for forcing (12).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a number of papers have studied R-tipping and related effects either using the theory of fast-slow dynamical systems 12,13 or notions from nonautonomous stability theory 2,14,15 . In particular, it has been suggested that local pullback attractors (where typical initial conditions are chosen from some open region in the distant past) provide a suitable setting to describe such transitions 2 . Further studies have attempted to provide early warning indicators for this type of tipping points [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%